Educação infantil e cultura lúdica: um olhar sobre a prática pedagógica das professoras da Escola de Aplicação da UFPA - MOCHIUTTI, Solange (2007)
The purpose of this work is to investigate the pedagogical practice of the teachers of child education of the School of Application of the UFPA has as focus of practical inquiry. The research looks for understand how time and the space are constituted to what concerned the ludic activities of child education and inquires which are the possibilities of the pedagogical practice of the teachers can offer from the manifestation of ludic situations. Considering playing as a basis of research the as social phenomenon, incursions had been carried on in the field of Sociology, chiefly in Benjamin (2002) and Brougère (1995, 1998) who characterize playing essential activity in the cultural and social development process of the child and in the contribution from Social Historic Psychology, chiefly in the works of Vygotsky (1984), Leontiev (1978), Elkonin (1998) who understand playing as a activity/need of the human being, considering the ludic situation the main source of the development and the most important activity of the child. This work refers also to the works of Kishimoto (1990, 1993, 1994, 1997, 1998b, 2001), Friedmann (1990,1996), Oliveira (1992), Campos de Carvalho; Rubiano (1994), Wajskop (1995, 1996) and Faria (1999a, 1999b), which focus the analysis of issues relating to the time and the space in the child education from the perspective of the child and the valorization of the ludic culture in the pedagogical practice. This work is a qualitative research, have approached social historic as guide of investigation and utilized the direct observation, inventory-questionnaire and the pedagogical project of the child education as an instrument to collect data. Such sources did allow the identification the presence of ludic daily activities in the institution. There are moments in the routine reserved to the entretainment, besides spaces and proper material for this purpose. There is also an understanding towards the organization of available spaces which may enrich the imaginary aspects of the ludic, artistic and creative. However, such procedures are used in a second plan in the pedagogical practice, considering that priority is driven to school-work activities. The homogeneity and the uniformity comprehend a great part of the format and the dynamics of the works there, performed, establishing in time and space rigidly institutcionalized by the school model. Therefore we must to reconsider this severe teaching and learning model, so that we may put the small child and its especificities and singularities as the main goal of all activity. This implies in the understanding of the ludic culture as social and cultural expression of the child and, as such, cannot be placed at a secondary position in the child education, rather to be included as a privileged activity and an excellent educative factor.